2016
DOI: 10.1093/nar/gkw691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of single nucleotide variants on transcription factor binding

Abstract: Diseases and phenotypes caused by disrupted transcription factor (TF) binding are being identified, but progress is hampered by our limited capacity to predict such functional alterations. Improving predictions may be dependent on expanding the set of bona fide TF binding alterations. Allele-specific binding (ASB) events, where TFs preferentially bind to one of the two alleles at heterozygous sites, reveal the impact of sequence variations in altered TF binding. Here, we present the largest ASB compilation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 61 publications
(83 reference statements)
2
54
1
Order By: Relevance
“…Our in-house allelic binding pipeline was used to extract reads at heterozygous sites from GM12878 datasets and assess mapability for filtering71. We obtained the genotype data of GM12878 from the 1000 Genomes Project72, and a personalized hg19 genome for GM12878 was built by representing single nucleotide variations as degenerate IUPAC codes (eg.…”
Section: Methodsmentioning
confidence: 99%
“…Our in-house allelic binding pipeline was used to extract reads at heterozygous sites from GM12878 datasets and assess mapability for filtering71. We obtained the genotype data of GM12878 from the 1000 Genomes Project72, and a personalized hg19 genome for GM12878 was built by representing single nucleotide variations as degenerate IUPAC codes (eg.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that taking advantage of specific biological insights ( e.g. identification of relevant TFs, reduction of genomic regions using functional genomic information) can significantly improve results, reducing the number of false positives [47,48] . In this respect, the evaluation set and case studies 3 and 4 focused on the analysis on TFs known to bind on the regions of interest, which enabled us to consistently evaluate the performance of the tool in the evaluation set, and further helped us to identify biologically relevant regulatory variants, affecting ePromoters function in case study 3, and VRN1 binding in barley in case study 4.…”
Section: Discussionmentioning
confidence: 99%
“…A) The number of heterozygous variants (x axis) within the same putative binding site will tend to have a greater impact on the TF binding probability when comparing haplotypes (weight difference, y axis). B) UCSC browser [48] screen shot, showing the locus of two SNPs that compose an heterozygous haplotype in one of the CEU individual, figure show the reference genome haplotype. The variants are located in the FUT10 promoter (top), variation-scan predicts an effect in three motifs that represent binding sites for GABPA, ETS1, ELF1 and ELK1, factors that have been proven to have binding sites in this region by the ENCODE project.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DNA sequence alterations that do not occur within regions that encode protein sequences directly (non‐coding mutations) represent ~ 98% of mutations in cancer and most still remain poorly characterized. Of these, mutations occurring in cis‐regulatory elements (i.e., enhancers and promoters) are of particular interest, as they can directly alter expression of associated gene products, by directly or indirectly altering DNA binding of TFs (Deplancke et al, ; Shi et al, ). Such mutations are frequent in breast cancer (Bailey et al, ; Zhou et al, ; Rheinbay et al, ; Gyorffy et al, ), but their significance is generally unclear (Nik‐Zainal et al, ).…”
Section: Altered Transcriptional Regulation In Human Breast Cancersmentioning
confidence: 99%